Antígenos naturais, recombinantes e sintéticos do Mycobacterium leprae e implicações diagnósticas na hanseníase - Lobato, Janaina (2011)
CHAPTER II: Objective: Our aim was to compare the performance of three serological assays in leprosy patients and their household contacts utilizing two quantitative ELISA tests using native PGL-I (PGL-1 ELISA), synthetic ND-O-HSA (ND-O-HSA ELISA), and the semi-quantitative lateral flow test (ML-Flow). Methods: Compare the performance of three immunological assays, PGL-I ELISA, ND-O-HSA ELISA, and ML-Flow were evaluated in 156 leprosy patients and 191 household contacts. Results: The sensitivity results of the PGL-1, ND-O-HSA, and ML-Flow were 68.83%, 63.65%, and 60.65%, respectively. The native and synthetic PGL-I ELISA assays detected antibodies in 22.73%, 31.82% of the paucibacillary (PB) patients, and the ML Flow test did not detect antibodies in this group. The ML-Flow test was able to discriminate patients into PB and multibacillary (MB) forms, while the native PGL-I and ND-O-HSA correlated with the bacillary load and the Ridley-Jopling clinical forms. In household contacts, the native PGL-I, ND-O-HSA, and ML-Flow assays detected seropositivity of 25%, 17%, and 10%, respectively. Conclusions: The use of ELISA and ML-Flow tests are thus recommended as additional tools in the diagnosis and classification of the clinical forms, aiding in prescribing the correct treatment regimen to prevent subsequent nerve damage and disability. CHAPTER III: Host pathogen interactions are mainly mediated by specialized molecules of the cell envelope. One of these essential mycobacterial cell wall components is the lipoarabinomannan (LAM). LAM has immunomodulatory roles, but its heterogeneity may be responsible for the differential immune response in leprosy patients and contacts. The research to structural motifs that could contribute as virulence factors and/or protective epitopes, and thereby derive effective biomarkers for diagnosis, drugs and/ or vaccines against leprosy has been very developed. Therefore, our aim was to develop specific mimetic peptides to this lipoglycan by using Phage Display of a random heptamer peptide library that may recognize a differential response in patients and contacts. We have used the anti-LAM CS-35 monoclonal antibody as a target for three rounds of selection. After sequencing and translation, peptides were pre-validated by ELISA and compared to the synthetic LAM-BSA antigen. The most reactive and repetitive peptide motif (A9) was subsequently tested against serum from 54 leprosy patients and 27 endemic controls by ELISA. The A9 phage-displayed peptide clone presented high levels of IgG antibodies in paucibacillary patients, from which 50% of them presented highly reactive sera. This reactivity has also been detected in tuberculoid, borderline-borderline and lepromatous patients. High levels of IgG1 were most frequent in endemic controls and reactional patients. On the other hand, the IgG profile and its subclasses in patients presented high levels of IgG and IgG2 and low levels of IgG1. The A9 clone presented a significant correlation with the synthetic LAM-BSA, for the IgG1 response. The highly reactive IgG response against the A9 clone was associated with the tuberculoid clinical form diagnosis, and detection of both IgG1 and IgG3 against this clone was associated with protection in endemic controls. CHAPTER IV: Heat Shock Proteins (HSPs), GroES and GroEL, are targets of strong human T-cell response, and a third of the cells responsive to M. leprae, recognize these proteins. Monoclonal antibodies mAbs CS-01 and CS-44 selected mimetic peptides that are ligands of their Fab portions, by phage display technique. Sera from 54 patients, 48 household contacts and 27 endemic controls were submitted to ELISA with B2 and A1 mimetic clones of the GroES and GroEL proteins, respectively, for detection of IgG and its subclasses. Using the mimetic clone of B2 GroES, the ELISA detected IgG antibodies present in sera of patients, contacts and endemic controls. The IgG antibodies were abundant in sera from multibacillary patients, especially in lepromatous (LL). A decline of IgG1 was found in patients and household contacts that became sick with leprosy and a raise of this subclass was present in sera of household contacts that did not develop the disease. With the mimetic clone of GroEL A1, the reactive antibodies were abundant in multibacillary patients, with a correlation with the bacillary load. In this study we observed that IgG antibodies against GroEL and GroES can be detected in the diagnosis of leprosy in serological tests produced with clones mimetics of these proteins. And the subclasses of IgG antibodies to GroES can demonstrate a targeting of antigenic molecules that induce the production of protective antibodies.